2005
DOI: 10.1016/s1808-8694(15)31332-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic profile of salivary gland neoplasms: analysis of 245 cases

Abstract: The data demonstrate that epidemiology profile of studied neoplasms corroborated the majority researched literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
39
5
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 7 publications
13
39
5
13
Order By: Relevance
“…This is in agreement with findings reported by some investigators [5,[12][13][14][15]. According to World Health Organization and some previous studies MEC is the most frequent malignant tumor and ACC is the second [1,3,4,6].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with findings reported by some investigators [5,[12][13][14][15]. According to World Health Organization and some previous studies MEC is the most frequent malignant tumor and ACC is the second [1,3,4,6].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previously published studies [3,[7][8][9][10][11][12], though other epidemiological studies showed a predominance of less than 60% for benign tumors [13,14]. Worldwide studies show geographic variation in the relative incidence of salivary gland tumors with differences in histological type [2,8].…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent in this study was adenoid cystic carcinoma. This is in agreement with findings reported by some investigators [7,11,13,15], but in contrast with other studies that reported mucoepidermoid carcinoma to be the most common malignant tumor [3, 8-10, 13, 14]. Adenocarcinoma NOS was the second most common malignant type, involving 5.8% of all tumors, as described by Ansari et al [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations